Directive Speech Acts in Learning Interactions in The School Environment for Students at State Junior High School 3 Mojosongo - Pristiawati, Eva Abripda; Wahyudi, Agus Budi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to determine the form and purpose of the director’s speech acts in the learning interactions of junior high school students as well as the factors that influence directive speech acts in the learning interactions of students at State Junior High School 3 Mojosongo. The data were analyzed using qualitative descriptive methods. The object of this research is directive speech acts. The technique used is listening and continuing with the katat technique. The subjects in this research were 25 class IX A students consisting of 15 girls and 10 boys. The results of this research found 21 utterances which were included in 8 types of directive speech acts consisting of these forms of speech acts, namely invitations as much as 15%, requests as much as 25%, bills as much as 13%, pressures as much as 5%, requests as much as 15%, suggestions as much as 10 %, orders as much as 12%, and giving instructions as much as 5%. The intent contained in a directive speech act is that it intends to invite as much as 20%, request as much as 25%, demand as much as 10%, urge as much as 5%, request as much as 8%, suggest as much as 15%, order as much as 10%, and give instructions as much as 7%. And finally, four factors were also found that influence directive speech acts in interaction learning at State Junior High School 3 Mojosongo, namely familiarity factors at 35%, age at 20%, speech situations at 30%, and psychology at 15%. From the results of this research, it is hoped that it can introduce the science of pragmatics which is applied in the learning process to assist in understanding the meaning or capturing the pragmatic meaning of speech situations, especially directive speech acts.